(3GdejQGKs - (3GdgQhj, GdGUagGfj, GdMGFQj, eMeO Jbj Hf MSjf Hf Ydj, J (B1299 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3Ef gPg fHPI eJYdbI HGMcGe GdejQGK cJHJgG dGjVGM SgGe cd hGMO ef GdhGQK aj cd eQJHI ef eQGJH GdfSH GdKdGK , aEf aj gPg GdeQGJH (B....s
(3BNQgG (B:s
... (3aJVY fGbI GdaMd GdKGfj CHhgG hCNhgG dCegG hGdPj cGf ef YegG dCfg GNh CHjgG hNGdgG dCfg CNh CegG (B.. (3GdfGbI GdVGef hjbGd GdUdHI hGdegLfI HfJ GdgLjf hgh GdPj CHhg TQja YJjb (B...s
(3JHUQI GdYfhGf (B:s
(3QSGdI aj GdejQGKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\179s
(3GdPQjYI (B23 - 186 ( 9079)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis